2003
DOI: 10.1152/ajplung.00005.2003
|View full text |Cite
|
Sign up to set email alerts
|

An in vitro airway wall model of remodeling

Abstract: Recent studies have shown that mechanical forces on airway epithelial cells can induce upregulation of genes involved in airway remodeling in diseases such as asthma. However, the relevance of these responses to airway wall remodeling is still unclear since 1). mechanotransduction is highly dependent on environment (e.g., matrix and other cell types) and 2). inflammatory mediators, which strongly affect remodeling, are also present in asthma. To assess the effects of mechanical forces on the airway wall in a r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
65
1

Year Published

2005
2005
2016
2016

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 75 publications
(67 citation statements)
references
References 32 publications
1
65
1
Order By: Relevance
“…We first sought to optimize culture conditions for epithelial ciliogenesis. Compared with our previous work (11,12), we found that the presence of calcium, ethanolamine, and phospho-ethanolamine as well as higher concentrations of retinoic acid (30 ng/ml) and bovine pituitary extract (200 g/ml) improved the extent of ciliogenesis and cilia length (Fig. 3).…”
Section: Resultscontrasting
confidence: 63%
See 4 more Smart Citations
“…We first sought to optimize culture conditions for epithelial ciliogenesis. Compared with our previous work (11,12), we found that the presence of calcium, ethanolamine, and phospho-ethanolamine as well as higher concentrations of retinoic acid (30 ng/ml) and bovine pituitary extract (200 g/ml) improved the extent of ciliogenesis and cilia length (Fig. 3).…”
Section: Resultscontrasting
confidence: 63%
“…It is likely that this increased susceptibility is at least partly caused by epithelial activation and damage and by factors including cytokines secreted by mesenchymal and inflammatory cells, which in turn cause loss of barrier function. However, asthmatic airways also experience compressive strain due to frequent brochocon- striction, and it has been demonstrated in vitro that mechanical compressive stress itself, at physiologically relevant levels, can activate the epithelium in asthmatic-like ways and induce airway wall remodeling events in the absence of inflammatory mediators (11,12,52,60,67,68).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations